Millennial Financial Crisis: A Review of the Role of Regulation in Online Lending - Renika Hasibuan; Muhammad Syafri; Vivid Violin (Sean Institute, 2024)
The millennial financial problem caused by online borrowing is urgent. Online loans are convenient yet risky due to high interest rates, aggressive debt collection, and lack of transparency. This crisis effects financial health, economic well-being, and societal issues, including financial stress-related mental health issues. Financial literacy and regulation are important to solving this problem. The Financial Services Authority (OJK) regulates to protect consumers, enhance transparency, and guarantee financial institutions meet requirements. Financial literacy can assist people comprehend internet lending risks and advantages and make smart financial decisions in addition to regulation. The attached research uses descriptive qualitative methods. This research analyses documents and literature to assess regulation efficacy, identify gaps, and propose a better regulatory framework. The results reveal that existing restrictions are often insufficient to protect customers from unethical lending activities, and low financial literacy contributes to lending decisions that worsen millennials' financial situations. Transparency, consumer protection, and financial awareness among millennials, especially about internet loans, are vital. The millennial financial problem requires effective regulation, financial knowledge, mental health help, and debt stigma reduction. To protect millennials' financial well-being, tighter industry norms and debt support measures are also advocated.